THE EFFECT OF GOLD PRICE FLUCTUATIONS ON CUSTOMER INTEREST IN GOLD INSTALLMENT INVESTMENTS - Mukhlis, Mukhlis; Romi, Muhammad; Mardiah, Azmi (UIN Raden Mas Said Surakarta, 2025)
Gold installment products at Bank Syariah Indonesia represent Sharia-compliant investment instruments that emphasize the principles of avoiding usury, gharar, maysir, and speculative practices, ensuring that transactions occur transparently and in accordance with Islamic financial ethics. This study aims to analyze the effect of gold price fluctuations on customer interest in investing in gold installment products at PT Bank Syariah Indonesia Duri Hangtuah Branch Office. This study uses a quantitative approach with a correlational research type to determine the relationship between the variable of gold price fluctuations (X) and customer interest in investing in gold installments (Y). The research sample consisted of 67 respondents selected through accidental sampling techniques. Data were obtained through questionnaires and analyzed using simple linear regression analysis with the help of SPSS version 25. The results show that gold price fluctuations have a positive and significant effect on customer interest, as evidenced by the calculated t-value of 9.513 > t-table 1.296 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) value of 0.582 indicates that 58.2% of the variation in customer interest is explained by gold price fluctuations, while the remaining 41.8% is influenced by other factors outside the model, such as promotions, investment risks, and financial literacy. This study contributes to the Islamic finance literature by empirically demonstrating that volatility in Islamic gold prices can increase customer interest. Practically, these findings suggest that Indonesian Islamic banks should utilize real-time gold price monitoring in their Sharia-compliant marketing and customer education strategies.